Folic acid-conjugated magnetic mesoporous silica nanoparticles loaded with quercetin: a theranostic approach for cancer management. Issue 39 (17th June 2020) - Mishra, Snehasis; Manna, Krishnendu; Kayal, Utpal; Saha, Moumita; Chatterjee, Sauvik; Chandra, Debraj; Hara, Michikazu; Datta, Sriparna; Bhaumik, Asim; Das Saha, Krishna
Abstract : pH-Sensitive quercetin/Fe3 O4 NPs loaded functionalized mesoporous SBA-15 fabricated for targeted drug delivery to colorectal carcinoma cells with high anti-carcinogenic efficacy. Abstract : The development of drug carriers based on nanomaterials that can selectively carry chemotherapeutic agents to cancer cells has become a major focus in biomedical research. A novel pH-sensitive multifunctional envelope-type mesoporous silica nanoparticle (SBA-15) was fabricated for targeted drug delivery to human colorectal carcinoma cells (HCT-116). SBA-15 was functionalized with folic acid (FA), and the material was loaded with the water-insoluble flavonoid, quercetin (QN). Additionally, acid-labile magnetite Fe3 O4 nanoparticles were embedded over the FA-functionalized QN-loaded monodisperse SBA-15 to prepare the highly orchestrated material FA-FE-SBA15QN. The in vitro and in vivo anti-carcinogenic efficacy of FA-FE-SBA15QN was carried out to explore the pH-sensitive QN release with putative mechanistic aspects. FA-FE-SBA15QN caused a marked tumor suppression, and triggered mitochondrial-dependent apoptosis through a redox-regulated cellular signaling system. Furthermore, FA-IO-SBA-15-QN initiated the c-Jun N-terminal Kinase (JNK)-guided H2AX phosphorylation, which relayed the downstream apoptotic signal to the phosphorylate tumor suppressor protein, p53. On the other hand, the selective inhibition of heat shock protein-27 (HSP-27) by FA-FE-SBA15QN augmented the apoptotic fate through JNK/H2AX/p53 axis. The in vitro and in vivo magnetic resonance imaging (MRI) studies have indicated the theranostic perspective of the composite. Thus, the result suggested that the newly synthesized FA-FE-SBA15QN could be used as a promising chemo theranostic material for the management of carcinoma.